Organocatalytic enantio- and diastereoselective cycloetherification via dynamic kinetic resolution of chiral cyanohydrins. Issue 1 (December 2017) - Yoneda, Naoki; Fujii, Yuki; Matsumoto, Akira; Asano, Keisuke; Matsubara, Seijiro
Abstract Enantioselective approaches to synthesize six-membered oxacycles with multiple stereogenic centres are in high demand to enable the discovery of new therapeutic agents. Here we present a concise organocatalytic cycloetherification for the highly enantio- and diastereoselective synthesis of tetrahydropyrans involving simultaneous construction of two chiral centres, one of which is fully substituted. This method involves dynamic kinetic resolution of reversibly generated chiral cyanohydrins. A chiral bifunctional organocatalyst selectively recognizes a specific chair-like conformation of the intermediate, in which the small steric effect of the linear cyano group as well as its anomeric effect play important roles in controlling stereoselectivity. The products offer additional utility as synthetic intermediates because the cyano group can be further transformed into a variety of important functional groups. This strategy provides a platform to design efficient approaches to obtain a wide range of optically active tetrahydropyrans, which are otherwise synthetically challenging materials. Enantioselective synthesis of six-membered oxacycles with multiple stereogenic centres is essential for the discovery of new therapeutic agents. Here the authors show organocatalytic cycloetherification for the highly enantio- and diastereoselective synthesis of tetrahydropyrans.